2008
DOI: 10.1007/s00134-008-1252-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of neuromuscular blockade on oxygen consumption in sedated and mechanically ventilated pediatric patients after cardiac surgery

Abstract: Objective: To measure the effect of intense neuromuscular blockade (NMB) on oxygen consumption (VO 2 ) in deeply sedated and mechanically ventilated children on the first day after complex congenital cardiac surgery. Design: Prospective clinical interventional study. Setting: Pediatric intensive care unit of an university medical centre. Measurements and results: Nine mechanically ventilated and sedated children (weight 2.8-8.7 kg) were included. All children were treated with vasoactive drugs. The level of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Vernon et al observed a modest reduction in O 2 of 8.7 ± 1.7% and that in energy expenditure of 10.3 ± 1.8% of pre-NMB values in 20 mechanically ventilated children of whom five had acute respiratory failure [41]. Lemson et al were unable to find any reduction in O 2 in pediatric cardiac surgery patients [42]. We observed a significant improvement in PaO 2 /FiO 2 in the presence of a fixed FiO 2 in patients with moderate or severe PARDS that could not be explained by an increase in EELV.…”
Section: Discussionmentioning
confidence: 99%
“…Vernon et al observed a modest reduction in O 2 of 8.7 ± 1.7% and that in energy expenditure of 10.3 ± 1.8% of pre-NMB values in 20 mechanically ventilated children of whom five had acute respiratory failure [41]. Lemson et al were unable to find any reduction in O 2 in pediatric cardiac surgery patients [42]. We observed a significant improvement in PaO 2 /FiO 2 in the presence of a fixed FiO 2 in patients with moderate or severe PARDS that could not be explained by an increase in EELV.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Bishop showed that paralysis with pancuronium did not change PaO2 or cardiac output [36]. Other more recent studies have also failed to show benefits in arterial oxygenation [37].…”
Section: Potential Benefits Of Nmbamentioning
confidence: 97%
“…They are recommended if effective mechanical ventilation cannot be achieved despite profound sedation [e.g., ARDS (77), severe asthma (25, 79)]. They are often used in case of severe cardio-vascular instability, but their benefit may be limited because only modest decrease in energy consumption is achieved compared to profound sedation (80, 81). Other common uses are refractory pulmonary and intracranial hypertension (82).…”
Section: Commonly Used Agentsmentioning
confidence: 99%